PERAN VARIABEL KEAKRABAN DALAM PENGGUNAAN E-COMMERCE PADA MODEL UTAUT - Tri Wulandari Ginting (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The research is focused on users of e-commerce. It is known that users of e-commerce are increasing, the use of technology, especially e-commerce, requires trust that comes from individuals or users. Later, with the trust that has arisen from individuals or users, the intention to use technology, especially e-commerce, will also increase. with the increasing use of technology, especially e-commerce. The familiarity variable functions as a variable that is able to strengthen the relationship between trust and behavioral intentions. The role of the intimacy variable becomes a moderating predictor variable which is a type of moderating variable that acts as a predictor variable in the relationship model formed. In order to find out how far the role of intimacy variables plays in the relationship between trust and behavioral intentions, a study was conducted with 400 respondents using the UTAUT model based on model fit measurement (PLS-SEM) and managed by SmartPLS. Where the main contribution of this study is the role of familiarity variables on trust and behavioral intention which has the result that intimacy variable is able to become a moderating variable that strengthens the relationship between trust variable and behavioral intention variable.